90 What Difference does Placement School Make? Contribution of School Characteristics to Professional Growth of Pre-Service Teachers - Koray Kasapoğlu; Ali Yıldırım (Anı Publishing, 2018)
Abstract. This qualitative phenomenological study attempted to gain insight into perceptions of pre-service teachers about the characteristics of placement schools in relation to their contributions to their professional growth. Collected through focus-group interviews with four groups, each consisting of six pre-service teachers who were in their last year in the program and had already taken practice courses at a public university in Turkey in the 2012-2013 academic year, qualitative data were then subjected to content analysis. The findings generated five major themes: conceptions of placement school, placement school characteristics, placement school experiences, contributions of placement schools to professional growth, and suggestions for placement school selection and experience. Pre-service primary school teachers tended to define the meaning of a better-served placement school that was equated with resource richness or abundance. However, the most striking finding from this study was that great placements were largely dependent on the quality of mentor teachers rather than other factors like resource richness or abundance in placement schools.